Development of speed and strength abilities of students in mini-football sectional classes - N. L. Nizhneva-Ksenofontova; N. N. Nizhneva; A. G. Mikhaylova (Вестник Северо-Кавказского федерального университета)
Introduction. Modern educational paradigm involves a sociocultural environment creation where there is a citizen’s formation as a subject of spiritual and intellectual self-development with ideology, values, and norms for the reality transformation. The relevance of the research problem is due to the need for high-quality professional training of future teachers.Goal. The article is aimed at considering a role of educational and ideological work in ensuring effective results of professional training (on the example of training foreign language teachers at universities in Belarus). The problem in the university education system is highlighted – the staged implementation of ideological support of the educational process.Materials and methods. The study is based on a theoretical analysis of scientific sources on the presented problem, as well as methods for studying the pedagogical experience of the Belarusian State University.Results and discussion. Priority directions in the organization of educational and ideological work in the professional development of specialists who ensure the spiritual and moral person’s development are identified in the course of the study. The results of the paper are aimed at solving the problems of high-quality professional training of a future foreign language teacher.Conclusion. Based on the results, we can conclude that professional training of foreign language teachers is possible if a set of conditions and requirements are taken into account: staged ideological work organized by the department must meet the goals and objectives of state policy; carried out systematically with the teaching staff, with students and staff, provide conditions for the formation of students’activity within the framework of socio-political events, and also include the creation a situation by the teacher that is optimal for the implementation of the intended tasks, in the process of preparing for direct activities with students and analysis of the work performed and modeling of ideological impact on future activities.